Concise and Practical Asymmetric Synthesis of a Challenging Atropisomeric HIV Integrase Inhibitor. (5th May 2015) - Fandrick, Keith R.; Li, Wenjie; Zhang, Yongda; Tang, Wenjun; Gao, Joe; Rodriguez, Sonia; Patel, Nitinchandra D.; Reeves, Diana C.; Wu, Jiang‐Ping; Sanyal, Sanjit; Gonnella, Nina; Qu, Bo; et al.
Abstract A practical and efficient synthesis of a complex chiral atropisomeric HIV integrase inhibitor has been accomplished. The combination of a copper‐catalyzed acylation along with the implementation of the BI‐DIME ligands for a ligand‐controlled Suzuki cross‐coupling and an unprecedented bis(trifluoromethane)sulfonamide‐catalyzed tert‐butylation renders the synthesis of this complex molecule robust, safe, and economical. Furthermore, the overall synthesis was conducted in an asymmetric and diastereoselective fashion with respect to the imbedded atropisomer.